Estudo de correlações tipo taxa de resfriamento x microestrutura x dureza da liga resistente ao calor 28Cr48Ni5W3Co - Silva, Wellington Anjos (Universidade Federal de São Carlos, 2022)
The 28Cr48Ni5W3Co alloy is widely used in furnace systems and various petrochemical plant equipment. In this work, the directional solidification of this alloy in a transient heat extraction regime was carried out, obtaining cooling rates according to the dendritic length-scales and enabling a correlation between both. An analysis was performed by sizing the secondary dendritic spacings (λ2) finding lower values (~ 16 m) near the metal/mold interface and higher values along the solidification direction (~ 120 m). The directionally solidified alloy casting showed an equiaxed morphology, with dendritic growth along its entire length. The thermodynamic analysis by CALPHAD method showed, from the Scheil model, that at the time of the first measurements with the thermocouples inside the casting there was no eutectic liquid present, resulting in rates that do not describe the beginning of solidification, but instead represent a global processing cooling rate. Within the range of the obtained cooling rates (from 0.03 ºC/s to 22 ºC/s), the analyzes revealed that increasing the cooling rate, in addition to reducing the secondary spacing, reduces the carbide size. The microstructure formed is composed of an austenitic matrix rich in nickel and chromium with carbides precipitated at the interdendritic portions. The secondary dendritic spacings were related to the cooling rate, and with this, an adjusted equation was generated that described the behavior of the microstructure along the casting. Finally, the Brinell hardness results indicated that there was a high correlation with the cooling rate.
Study of correlations type cooling rate x microstructure x hardness of the heat resistant 28Cr48Ni5W3Co alloy
Keywords: 28Cr48Ni5W3Co; Directional solidification; Microstructures; Interdendritic spacing; Cooling rate; Heat resistant alloys; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA